Optimizing the Handling of Traffic Accidents by the Law Enforcement Unit of the Demak Resort Police Traffic Unit to Achieve Traffic Security, Safety, Order, and Smoothness - Kurnia, Jason (Advances in Police Science Research Journal, 2024)
Currently, traffic problems that occur in Demak Resort Police are increasingly complex and ongoing. One of them is the high number of traffic accidents. However, the handling of traffic accidents carried out by the Law Enforcemet Unit of the Demak Resort Police Traffic Unit is still considered not optimal in realizing traffic security, safety, order, and smoothness. The purpose of this research is to describe the actualization and optimalization of traffic accidents handling to achieve traffic security, safety, order, and smoothness. The concepts used include optimization, traffic accidents, traffic accident handling, Law Enforcement Unit of the Traffic Unit, traffic security, safety, order, and smoothness, coordination, and collaboration. The theories used are management theory, competence, FFA (Force Field Analysis), and The Why/Why Diagram analysis. This research is a qualitative study with a type of field research that takes data through interviews, observations, document studies, and Focus Group Discussions (FGD) to a number of sources. The results showed that (1) the actualization of traffic accident handling needs to be optimized through increased socialization, coordination, collaboration, and personnel competence. In addressing these issues, the author has created educational stickers and comedy video of Polri 110 Call Center service, brochures and standing banner of traffic accident handling mechanisms, as weel as a criticism and suggestion box. Furthermore, the author coordinated with the Security and Safety Unit, Integrated Police Service Center, Public Relations, and Community Guidance Unit of the Demak Resort Police to help disseminate the products. In addition, the author has also coordinated with the Regulation, Guarding, Escorting, and Patrolling Unit to utilize the e-turjagwali application and strengthen collaboration with the Quick Response Task Force. On the other hand, this unit also needs to revise SOP and Job Description, revise the budget, utilize operational support funds, and apply for R4 vehicles. (2) Handling of traffic accidents, especially in personnel competence, can be optimized by providing formal education to members. The author has also made pocket books and short educational video on handling traffic accidents, conducted coaching clinics, member skills training, and sharing sessions.